2000
DOI: 10.1021/ja993448c
|View full text |Cite
|
Sign up to set email alerts
|

Cyanomethylene Formation from the Reaction of Excited Nitrogen Atoms with Acetylene:  A Crossed Beam and ab Initio Study

Abstract: The reaction of excited nitrogen atoms, N( 2 D), with the simplest alkyne, C 2 H 2 , was investigated for the first time under single-collision conditions in crossed beam experiments with mass spectrometric detection. The experimental results combined with electronic structure calculations and RRKM predictions allow us to identify cyanomethylene (HCCN) as the main primary reaction product and to establish its formation dynamics. The identification of the N/H exchange channel suggests that the title reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 39 publications
(58 reference statements)
7
85
0
Order By: Relevance
“…HC(N)CH can then either decompose to cyclic-HC(N)C + H or isomerize to HCCNH and/or H 2 CCN (cyanomethyl). Both HCCNH and H 2 CCN can dissociate into HCCN + H. Crossed beam experiments have been performed by Balucani et al (2000a) and the results are consistent with both HCCN + H and cyclic-HC(N)C + H formation. Unfortunately, the difference in the energetics of the two channels does not allow a clear discrimination between these products, but some arguments are in favor of HCCN formation.…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 57%
See 2 more Smart Citations
“…HC(N)CH can then either decompose to cyclic-HC(N)C + H or isomerize to HCCNH and/or H 2 CCN (cyanomethyl). Both HCCNH and H 2 CCN can dissociate into HCCN + H. Crossed beam experiments have been performed by Balucani et al (2000a) and the results are consistent with both HCCN + H and cyclic-HC(N)C + H formation. Unfortunately, the difference in the energetics of the two channels does not allow a clear discrimination between these products, but some arguments are in favor of HCCN formation.…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 57%
“…Unfortunately, the difference in the energetics of the two channels does not allow a clear discrimination between these products, but some arguments are in favor of HCCN formation. RRKM estimates (Balucani et al 2000a) based on the ab initio potential energy surface calculations confirmed that the channels leading to HCCN + H and cyclic-HCCN + H are the main pathways, with branching ratios σ (HCCN + H)/σ (cyclic-HCCN + H) estimated to be 86:14 and 77:23 at E CM = 0.135 and 0.42 eV, respectively. By extrapolating this variation, we thus recommend a branching ratio of (0.9 ± 0.1)/(0.1 ± 0.05) at 300 K, as well as at 150 K. Table 3).…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, we added 19 reversible reactions to the C/H/O/N mechanism, which describe the kinetics of O( 1 D) and N( 2 D), including radiative and collisional desexcitation. These reactions rates are taken (or have been estimated) from Okabe (1978), Herron (1999), Umemoto et al (1998), Balucani et al (2000a), Sato et al (1999), Balucani et al (2000b), and Sander et al (2011).…”
Section: Excitation Of Oxygen and Nitrogen Atomsmentioning
confidence: 99%
“…The key motivation for this is the need for modeling the reentering of spacecrafts landing on the solar planets whose atmosphere contains a large amount of nitrogen. [1][2][3][4][5][6][7] This implies the need for calculating extended matrices of accurate detailed rate coefficient values of the various processes of reaction ͑1͒. In spite of that, for this reaction only little experimental information [8][9][10] on the dependence of the rate coefficients from the temperature is available.…”
Section: Introductionmentioning
confidence: 99%